(untitled) (Journal of Dhaka Medical College, 2010)
The study was carried out to know the pattern of dermatoses among admitted patients in skin inpatient department from March 2009 to February 2010 in Dhaka Medical College Hospital. A total of 244 patients (124 female & 120 male) were admitted during this study period. Exfoliative dermatitis 52(21.31%) were the most commonest dermatoses, followed by Psoriasis vulgaris 28(11.47%), Pemphigus vulgaris 20(8.19%), Stevens Johnson Syndrome 20(8.19%), Bullous pemphigoid 16(6.55%), Erythema multiforme 16(6.55%), Systemic lupus erythematosus 12(4.91%), Scrofuloderma 12(4.91%), Scleroderma 12(4.91%), Darier’s disease 8(3.27%), Vasculitis 8(3.27%), Psoriatic arthopathy 8(3.27%), Pemphigus vegetans 4(1.63%), Lupus vulgaris 4(1.63%), Tuberculosis verrucosa cutis 4(1.63%,), Herpes zoster 4(1.63%), Erythema annulare centrifugum 4(1.63%), Chronic bullous disease of childhood 4(1.63%), Xanthoma tuberosum 4(1.63%). Mycosis fungoides 3(1.22%), Sezary syndrome 1(0.40%). Key words: Pattern of dermatoses; prevalence. DOI: 10.3329/jdmc.v19i1.6251 J Dhaka Med. Coll. 2010; 19(1) : 43-46.